Protective Effect of Akkermansia muciniphila against Immune-Mediated Liver Injury in a Mouse Model - Wu, Wenrui; Lv, Longxian; Shi, Ding; Ye, Jianzhong; Fang, Daiqiong; Guo, Feifei; Li, Yating; He, Xingkang; Li, Lanjuan (Frontiers in Microbiology, 2017)
Accumulating evidence indicates that gut microbiota participates in the pathogenesis and progression of liver diseases. The severity of immune-mediated liver injury is associated with different microbial communities. Akkermansia muciniphila can regulate immunologic and metabolic functions. However, little is known about its effects on gut microbiota structure and function. This study investigated the effect of A. muciniphila on immune-mediated liver injury and potential underlying mechanisms. Twenty-two C57BL/6 mice were assigned to three groups (N=7-8 per group) and continuously administrated A. muciniphila MucT or PBS by oral gavage for 14 days. Mouse feces were collected for gut microbiota analysis on the fifteenth day, and acute liver injury was induced by Concanavalin A (Con A, 15 mg/kg) injection through the tail vein. Samples (blood, liver, ileum, colon) were assessed for liver injury, systemic inflammation, and intestinal barrier function. We found that oral administration of A. muciniphila decreased serum ALT and AST and alleviated liver histopathological damage induced by Con A. Serum levels of pro-inflammatory cytokines and chemokines (IL-2, IFN-γ, IL-12p40, MCP-1, MIP-1a, MIP-1b) were substantially attenuated. A. muciniphila significantly decreased hepatocellular apoptosis; Bcl-2 expression increased, but Fas and DR5 decreased. Further investigation showed that A. muciniphila enhanced expression of Occludin and Tjp-1 and inhibited CB1 receptor, which strengthened intestinal barriers and reduced systemic LPS level. Fecal 16S rRNA sequence analysis indicated that A. muciniphila increased microbial richness and diversity. The community structure of the Akk group clustered distinctly from that of mice pretreated with PBS. Relative abundance of Firmicutes increased, and Bacteroidetes abundance decreased. Correlation analysis showed that injury-related factors (IL-12p40, IFN-, DR5) were negatively associated with specific genera (Ruminococcaceae_UCG−009, Lachnospiraceae_UCG−001, Akkermansia), which were enriched in mice pretreated with A. muciniphila. Our results suggested that A. muciniphila MucT had beneficial effects on immune-mediated liver injury by alleviating inflammation and hepatocellular death. These effects may be driven by the protective profile of the intestinal community induced by the bacteria. The results provide a new perspective on the immune function of gut microbiota in host diseases.